Improving Ergonomic Interventions to Reduce Whole-Body Vibration Exposures among Professional Drivers - Blood, Ryan Patrick (My University, 2013)
Assessing physical exposures in occupational health studies proves challenging regardless of the industry. In transportation, however, the problem is exacerbated by the fact that subjects are literally on the move. To improve the understanding of the link between chronic whole-body vibration exposure and adverse health outcomes, this study evaluated epidemiologic trends, comparing injury events among employees in a large metropolitan transit agency. The epidemiology results indicate that bus drivers are at increased risk for injury compared to a referent group of administrative workers. This study also presents the technological advancements in field-based, whole-body vibration (WBV) exposure assessment by comparing three generations of WBV data collection equipment. This study presents the ISO 2631 Part 1 and Part 5 results for field-based WBV exposure studies among professional truck drivers, bus drivers, and heavy equipment operators. Finally, this study applied field-collected vibration signal data to research on a vibration simulation hexapod. The final phase of this study evaluated vibration attenuation, comparing the current industry standard (an air-ride suspension seat) to a newly developed technology (an electromagnetically active seat) across city streets, freeways, and rough roads. This comparison of seat suspension technologies was conducted for evaluation between professional truck drivers and bus drivers, and it included a measure of vibration transmission through the spines of subjects. The results indicate that the electromagnetically active seat is a promising engineering control that may prevent injuries over the long term. This study combined several research approaches that are important to the field of occupational health. The goal of this research was to improve the understanding of injury risk and intervention options, with the ultimate goal of improving the lives of professional bus drivers.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: Engineering Controls; Ergonomics; Industrial Hygiene; Low Back Pain; Occupational health; Health sciences; Epidemiology; environmental health